Development Strategy Group Craftsman in Serang - Elvin Bastian; Muhamad Fakhrudin; Widya Nur Bhakti Pertiwi (PT. EQUATOR SINAR AKADEMIA, 2022)
Research objectives this is for formulate what strategies can be used for developing group craftsman gold in Serang. Group craftsman gold in Serang centered in Taktakan. During here. craftsmen depend on the order of the gold shop in Serang. Study this character descriptive qualitative with SWOT analysis. Research results put forward that for develop craftsman industry gold Taktakan. defensive strategy needed for minimize weaknesses and anticipate threat.